2010
DOI: 10.1002/aqc.1123
|View full text |Cite
|
Sign up to set email alerts
|

Biomass removal by dolphins and fisheries in a Mediterranean Sea coastal area: do dolphins have an ecological impact on fisheries?

Abstract: ABSTRACT1. Dolphins are often claimed to compete with fisheries, including through removal of substantial biomass. To calculate the biomass removed by fisheries and the degree of resource overlap with dolphins in a coastal area of Greece, estimates of dolphin abundance based on photographic capture-recapture were combined with an assessment of fishing effort and catch.2. The estimated total biomass consumed annually by local dolphin populations -15 short-beaked common dolphins and 42 common bottlenose dolphins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
65
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(71 citation statements)
references
References 48 publications
6
65
0
Order By: Relevance
“…This feeding strategy has most likely been adopted by bottlenose dolphins to increase their feeding rate, while decreasing the energy expenditure associated with foraging (Fertl & Leatherwood 1997), in order to compensate for the lack of fish prey in the surrounding waters. Recent studies have demonstrated how overfishing has caused detrimental effects on fish stocks in the study area , Gonzalvo et al 2010, including important prey of bottlenose dolphins (Bearzi et al 2010a). It is possible that a decrease in the availability of prey prompted the behaviorally flexible and opportunistic bottlenose dolphin to focus (at least in part) on fish resources located around fish farm cages.…”
Section: Discussionmentioning
confidence: 99%
“…This feeding strategy has most likely been adopted by bottlenose dolphins to increase their feeding rate, while decreasing the energy expenditure associated with foraging (Fertl & Leatherwood 1997), in order to compensate for the lack of fish prey in the surrounding waters. Recent studies have demonstrated how overfishing has caused detrimental effects on fish stocks in the study area , Gonzalvo et al 2010, including important prey of bottlenose dolphins (Bearzi et al 2010a). It is possible that a decrease in the availability of prey prompted the behaviorally flexible and opportunistic bottlenose dolphin to focus (at least in part) on fish resources located around fish farm cages.…”
Section: Discussionmentioning
confidence: 99%
“…Accurate determination of the diet of marine mammals is essential for assessing ecological interactions and potential effects on prey populations (Bowen 1997, Kenney et al 1997, Trites et al 1997, DeMaster et al 2001, Bearzi et al 2010. Traditional measures of diet determination, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…One general index that is used as a measure of resource overlap between two species occupying the same niche and which may be adapted to assess the degree of prey-species overlap between the CBD's stomach contents and bottom trawl fishery catches (Bearzi et al, 2010) is a modification of the Pianka niche overlap index a (Pianka, 1974):…”
Section: Stomach Contentmentioning
confidence: 99%